2015
DOI: 10.1177/0269215515570379
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for the treatment of chronic low back pain: a systematic review and meta-analysis of randomised controlled trials

Abstract: Our results found a beneficial effect for strength/resistance and coordination/stabilisation exercise programs over other interventions in the treatment of chronic low back pain and that cardiorespiratory and combined exercise programs are ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
368
1
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(401 citation statements)
references
References 68 publications
12
368
1
20
Order By: Relevance
“…In addition Kamioka et al [28] reported that there was strong evidence that in a healthy population Pilates exercise improved flexibility and enhanced muscular endurance in the short term. While our study did not specifically measure TrA contraction Searle et al [36] noted that isolated training of TrA led to an earlier onset of TrA activation which reflected a more constant activation pattern that is observed in healthy individuals. The increase in CE found in our study could not be attributed solely to TrA and MF contraction as the method of testing recruited both global and local musculature which was not specifically trained in the intervention.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition Kamioka et al [28] reported that there was strong evidence that in a healthy population Pilates exercise improved flexibility and enhanced muscular endurance in the short term. While our study did not specifically measure TrA contraction Searle et al [36] noted that isolated training of TrA led to an earlier onset of TrA activation which reflected a more constant activation pattern that is observed in healthy individuals. The increase in CE found in our study could not be attributed solely to TrA and MF contraction as the method of testing recruited both global and local musculature which was not specifically trained in the intervention.…”
Section: Discussionmentioning
confidence: 84%
“…We cannot infer causation using the current study design nor did we investigate mechanisms of action associated with Pilates exercise although the improvements in functional disability may be suggestive of muscle recruitment (TrA, MF) which enhance static and dynamic posture [13]. In a review of exercise interventions for LBP Searle et al [36] reported that interventions with an emphasis on isometric contractions of TrA contributed to lumbo-pelvic stability when stability was challenged. Furthermore Rio et al [37] observed that isometric contractions of the quadriceps femoris induced greater immediate analgesia in patella tendonopathy patients compared to concentric eccentric contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Although some therapeutic interventions have demonstrated benefits, researchers have not quantified or characterized the results yielded by specific non-surgical interventions [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have suggested that exercise programs are effective in the treatment of LBP [9][10][11][12]; however, most researchers fail to provide evidence favoring one exercise over another. Contradicting results might be related to poor sensitivity of the instruments, an unmatched research design, small sample sizes, and/or the lack of a valid and reliable index for standardization.…”
Section: Comprehensive Balance Parametersmentioning
confidence: 99%
“…AlĂ©m disso, os Testes FĂ­sicos Funcionais (TFF) tambĂ©m podem fornecer parĂąmetros sobre estabilidade lombo-pĂ©lvica, jĂĄ que indivĂ­duos com dor lombar tendem a apresentar comprometimento na capacidade fĂ­sica e funcional. Algumas dessas alteraçÔes sĂŁo: hipotrofia muscular, menor resistĂȘncia e força muscular [10][11][12] , dĂ©ficit proprioceptivo 13 , alteraçÔes de extensibilidade muscular e no controle motor 10,14 . Para avaliar a capacidade fĂ­sico-funcional da regiĂŁo lombo--pĂ©lvica, diferentes testes podem ser encontrados na literatura [15][16][17] .…”
Section: Introductionunclassified